2021
DOI: 10.3390/ani11041119
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Starling Population, Estimation and Mapping of the Damage to Olive Crops in the Apulia Region

Abstract: The presence of wildlife in areas with a high concentration of farming activities can create a conflict between conservation objectives and productive purposes. Near Brindisi (Apulia, S-E Italy), a substantial amount of cash compensation claims for damages reported by local farmers and attributed to starlings (Sturnus vulgaris) has been registered. The aim of this study was to quantify the starling population wintering in the Apulia region, in order to assess the potential damage to crop production caused by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(22 reference statements)
0
0
0
Order By: Relevance
“…The European Starling (Sturnus vulgaris), originally native to Europe and North Africa, was introduced to the Americas in the late 19th century, where it rapidly established colonies [16]. The species causes considerable damage to local agriculture in Italy [17], and has been found to pose a disease risk to livestock in the U.S. [18]. Studies on the island of Hawaii have shown that exotic birds alter the plant seed dispersal patterns [19].…”
Section: Introductionmentioning
confidence: 99%
“…The European Starling (Sturnus vulgaris), originally native to Europe and North Africa, was introduced to the Americas in the late 19th century, where it rapidly established colonies [16]. The species causes considerable damage to local agriculture in Italy [17], and has been found to pose a disease risk to livestock in the U.S. [18]. Studies on the island of Hawaii have shown that exotic birds alter the plant seed dispersal patterns [19].…”
Section: Introductionmentioning
confidence: 99%
“…Common Starlings are flexible in choosing a location to establish a roost. Roost site locations are often concentrated in farmland that heavily fragments natural areas and contains a variety of crops as possible food sources, but they can also be found near population centers [25][26][27] Roosting site fidelity has been reported to be between 48% and 95%, with fidelity increasing with the age of the bird and availability of feed near the roosting site [28][29][30]. This pattern of roost site fidelity is also seen on a smaller scale, with starlings preferring to stay in one roost site overnight unless their energetic needs increase due to cold weather or a lack of an easily available food source [31].…”
Section: Introductionmentioning
confidence: 99%